Corporate Governance and Executive Compensation in China - Li, Xiaoxue (2019)
Abstract In order to improve the effectiveness of compensation performance contract and alleviate the agency problem, many scholars at home and abroad pay more attention to the topic of corporate governance structure. In addition, due to different economic environment and economic conditions, foreign research results are not applicable to domestic companies because there are some differences in corporate governance structure between China and foreign countries. Therefore, this paper analyzes the influence of governance structure on executive compensation by using the data of listed companies in China.